Failure of Patellar Plating with Mini-Fragment Implants: A Case Report. Issue 1 (January 2017) - Miles, Daniel T.; Graves, Matthew L.; Spitler, Clay A.; Bergin, Patrick F.
Abstract : Case: A 40-year-old woman presented to the emergency department with a comminuted fracture of the patella with separation of the bone fragments. The patient underwent an open reduction and osteosynthesis using medial and lateral 2.0-mm nonlocking plates, which subsequently led to pain in the anterior and posterior aspects of the knee. Conclusion: In this patient, bicolumnar nonlocking plating was unable to adequately resist the tensile forces of the extensor mechanism. We believe that the probable cause of failure was an insufficient neutralization of the tensile forces exerted by the extensor mechanism. Because of the substantial forces acting on the patella, a method of converting these tensile forces into compressive forces is very beneficial, as seen with anterior tension-band wiring. Although we used nonlocking plates in our patient, we believe that locking-plate fixation placed along the medial and lateral columns also would have had a biomechanical disadvantage in dispersing the tensile forces exerted by the extensor mechanism.